Agriculture, environment and society in the European Union and Japan - Izacara Palacios, Simón Pedro (Libros UAT, 2018)
Both in the European Union and in Japan, for decades agriculture was contemplated as an activity that in harmony with nature, contributed to the conservation and enrichment of the rural environment. That is why during this period the idea of ??regulating agricultural activity from the environmental point of view was not raised. However, during the last two decades there has been a gradual change in public opinion, both European and Japanese, which has resulted in a rejection of intensive agricultural practices that pollute the natural environment. With the entrance to the new millennium, in a progressive frame rejection of the consumers makes the dominant model of intensive agriculture and of increasing demand of foods of high ecological quality; to which it is necessary to unite a change in the international agrarian trade, where the primacy of the domestic policies is eclipsed by a process of agrarian liberalization and rejection of the protectionist practices, the agrarian policies of Japan and the European Union embark on a new course, finding in the empowerment of the extraproductive functions of agriculture and the pursuit of environmental objectives, a new way for public intervention.